The Role of Parents in Guiding Children's Learning Activities at Home - Pusparini, Gita Asih; Pamujo, Pamujo; Wijayanti, Okto (Journal of Innovation and Research in Primary Education, 2022)
This study aims to determine the role of parents in guiding learning activities from home in fourth-grade elementary school students. This type of research is descriptive qualitative research. This research was conducted at SDN Kaliwadas 01. The source of data used was primary data using interviews with teachers, parents and students, and secondary data in the form of documentation. The informant selection technique in this study used a purposive sampling technique. Analysis of the data used in this study using an interactive analysis model from Miles and Huberman which consists of data collection, data reduction, data presentation, and drawing conclusions. The results of this study on the role of parents in guiding learning activities from home during the covid-19 pandemic, the results of interviews, observations, and documentation regarding the role of parents in learning from home, there are several problems found in parents when guiding learning activities from home, some of these problems can conclude in this study: the lack of students in understanding the material so that it requires parents to study material that is not in their field, limited facilities, especially in terms of quotas, parents' educational backgrounds. The active role of parents in mentoring learning, directing children to study well, limiting children from playing with gadgets and parents providing facilities for children.